ANALISIS PENGARUH KUALITAS PRODUK, KUALITAS LAYANAN, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Pemakai Smartphone Merek Samsung di SMS Shop Kota Semarang) - Fatkur Rahman, 12.05.51.0121; ., Kasmari (Students' Journal of Economic and Management, 2016)
In order to maintain and increase sales, every company needs to hold the resulting product development efforts toward higher quality, thus providing effective, satisfying power and greater appeal. How and supplying the right product for the intended market, can satisfy its customers and can increase profits in the long run through increased sales. This study aimed to analyze the effect of product quality, service quality, and the perception of price on purchase decisions Brand Samsung Smartphone in SMS Shop Semarang. This research is descriptive. The total sample are 100 respondents. The research instrument used questionnaire. Analysis of data using multiple linear regression. The results showed that in partial analysis are variables product quality influence on purchasing decisions, quality of service influence on purchasing decisions, and the price perception influence on purchase decisions. Together variables are product quality, service quality, and price perception influence on purchasing decisions. Keywords    : product quality, service quality, price perception, purchasing decisions